2016
DOI: 10.1021/acs.jafc.6b02296
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Amylomaltase from Corynebacterium glutamicum

Abstract: Amylomaltase is an essential enzyme in maltose utilization and maltodextrin metabolism, and it has been industrially used for the production of cyclodextrin and modification of starch. We determined the crystal structure of amylomaltase from Corynebacterium glutamicum (CgAM) at a resolution of 1.7 Å. Although CgAM forms a dimer without NaCl, it exists as a monomer in physiological concentration of NaCl. CgAM is composed of N- and C-terminal domains, which can be further divided into two and four subdomains, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 48 publications
0
41
1
Order By: Relevance
“…Our results may contradict previous reports on the diet of these birds indicating their capacity to select plants (or parts of plants) with high-nutritional value (low in fiber) in all periods [1,8]. However, the high presence of GH families encompassing genes for the degradation of starch (e.g.GH77, with amylomaltase activity [59]) (Table 3), and genes involved in starch metabolism (e.g. starch phosphorylase [EC.2.4.1.1]) also indicates that starch-containing compounds may constitute an important part of the nutrition in the wild ptarmigan diet.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results may contradict previous reports on the diet of these birds indicating their capacity to select plants (or parts of plants) with high-nutritional value (low in fiber) in all periods [1,8]. However, the high presence of GH families encompassing genes for the degradation of starch (e.g.GH77, with amylomaltase activity [59]) (Table 3), and genes involved in starch metabolism (e.g. starch phosphorylase [EC.2.4.1.1]) also indicates that starch-containing compounds may constitute an important part of the nutrition in the wild ptarmigan diet.…”
Section: Discussioncontrasting
confidence: 96%
“…In comparison with CGTase that mainly produces small ring cyclodextrins (SR-CDs) with 6-8 mer, AM showed fewer number of domains [49,50]. EcAM [51] and CgAM [52] share only 30% identity of protein sequences but both of them similarly represent an additional N-terminal domain, so-called domain N (Figure 1B). The subdomains N1 and N2 are linked by a short linker of nine amino acid residues.…”
Section: Overall Structure Of Amylomaltasementioning
confidence: 99%
“…They are characterized by the presence of a N -domain of about 160 amino acids in front of the TIM-barrel catalytic domain. Phyre2 analysis showed that the A. cellulolyticus sequence can be folded in a 3D model with 100% confidence with the structure of the amylomaltase from the bacterium C. glutamicum [ 7 ]. The percentage of identity of the two sequences is about 42%.…”
Section: Structural Analysesmentioning
confidence: 99%
“…The percentage of identity of the two sequences is about 42%. A possible role of the N -terminal domain could be that of a carbohydrate-binding module (CBM) as the presence of an immunoglobulin-like β-sandwich fold would suggest [ 7 ]. Currently, the A. cellulolyticus enzyme is the only extreme amylomaltase possessing the N -terminal domain to have been expressed as a recombinant protein and functionally tested.…”
Section: Structural Analysesmentioning
confidence: 99%
See 1 more Smart Citation